Strategi Penataan Lahan BUMDes Puntukrejo Ngargoyoso Karanganyar, Sebuah Penerapan Konsep Agrowisata - Musyawaroh Musyawaroh; Tri Joko Daryanto; Ummul Mustaqimah (ARSITEKTURA, 2021)
This paper discusses a land management strategy that applies agritourism in BUMDes land in Puntukrejo Village, Karanganyar Regency. An appropriate planning strategy is necessary to manage the village's agricultural potencies supported by topographic beauty, cool microclimate, and various well-known products. This village also has BUMDes relatively wide land assets but is not utilized properly. The agritourism applied in land assets usage is expected to increase rural tourism visits by exposing agricultural activities. The case study method is used in this process because it has suitability, especially in researching a strategy to obtain answers to the question "how" and its argument "why." The analysis process is done descriptively qualitatively. The study identifies community activities and village potencies for determining various tourism activities and resolves land-use allocation. The result is applying agritourism that utilizes the attractiveness of agriculture by displaying the potential of fertility and natural beauty and supporting leading agricultural commodities, facilities, and harmony by equipping supporting facilities for the convenience of visitors supporting infrastructure by providing unique icons.